Behind open doors: Patient privacy and the impact of design in primary health care, a qualitative study in Indonesia - Pratiwi, Agnes Bhakti; Padmawati, Retna Siwi; Willems, Dick L. (Frontiers in Medicine, 2022)
Background The importance and attention to patient privacy in recent decades have been directed mostly toward medical data protection in electronic means. Hence, other aspects of patients’ privacy were overlooked, particularly in the primary health care (PHC) level. In the attempt of many countries, including Indonesia, to strive toward universal healthcare provision, a strong and accessible PHC is essential. This situation may create a tension in privacy provision where patients who need to disclose secrets may opt for other facilities, such as hospitals. This study aimed to describe and discuss patients’ and doctors’ perspectives and experiences about privacy in PHC in Indonesia, particularly since the universal coverage started. Design and methods We used in-depth interviews and observations to gather information. Inductive and thematic data analyses were conducted. We interviewed PHC users (n = 17), doctors (n = 16), other PHC staff (n = 7), and non-PHC users (n = 5) and observed the PHC activities. Results We found that privacy is imperative for both patients and doctors. Design and conditions in PHC, including consultation room doors open, separate rooms for treatment, and patients’ symptoms asked by other staff were aspects that undermine privacy in PHC. Inadequate physical and informational privacy protection during a patient’s visit has affected the quality of care negatively in ways that impede proper anamneses and physical examination. Conclusion Ensuring patients’ and doctors’ physical and informational privacy is essential to creating PHC as the primary source of care that responds to the privacy values of its users, but it has been overlooked. The PHC building designs and care provision guidelines should incorporate the privacy needs of patients and doctors.